Practice and Exploration in Shenzhen Rail Transit Planning and Construction - WANG Yuanhui (Chengshi guidao jiaotong yanjiu)
［Objective］ As a mega city, Shenzhen has entered a new stage of development, and its rail transit is facing new development requirements, shifting from pursuing speed and scale to focusing more on quality and effectiveness. In order to promote the high-quality development of Shenzhen urban rail transit, it is necessary to lead high-quality development through high-level planning, improve the rationality of planning schemes, and reasonably grasp the implementation rhythm. ［Method］ Status and implementation effects of previous phases of Shenzhen rail transit planning construction are reviewed and summarized. On one hand, the experience and issues of urban rail transit network planning in terms of network structure, functional hierarchy, and network scale are summarized; on the other hand, the effectiveness of Shenzhen rail transit construction planning is summarized in terms of supporting urban development, meeting transportation needs, innovating investment and financing models, and property development. Aiming at the problems existing in the early planning, suggestions are put forward to guide subsequent urban rail transit planning and construction. ［Result & Conclusion］ A visionary long-term urban rail transit network is the basis for promoting rail transit planning and construction; grasping the city′s development prospects is the premise of a stable rail construction plan; strengthening the research on urban rail transit investment and financing models and investment benefits is an important means to promote the sustainable development of urban rail transit. All in all, the implementation path of inter-city rail transit in Shenzhen metropolitan area should be explored to further enhance the leading role of rail transit in the development of metropolitan area.